Prototipo de planchas de tumbado de yeso reforzado con cal, cascarilla de arroz, fibra de coco y fibra de plátano - Mosquera Bonilla, Roxana Jazmín (2025)
This study presents the development of a prototype gypsum ceiling panel reinforced with rice husk and banana fiber, as a sustainable alternative to conventional materials used in construction. Although in recent years there has been significant progress in environmental care and conservation, little attention has been given to the issue of agricultural waste generated during the harvesting process, which often accumulates without proper management. The accumulation of this waste has a negative impact in several areas. On the one hand, it affects soil and water quality, deteriorating ecosystems, and on the other, it impacts the health of people who depend on these resources. With this prototype, we aim to partially replace traditional construction materials, such as cement, by incorporating biocomposites, specifically rice husk and plant fibers such as banana and coconut. These materials are abundant, low-cost, and possess favorable mechanical properties. The fibers serve as reinforcement for gypsum, increasing the panel’s strength and durability, while also contributing to the energy efficiency of buildings by improving thermal insulation.........